PENGARUH LIKUIDITAS, KOMPLEKSITAS OPERASI PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS PERUSAHAAN TERHADAP AUDIT REPORT LAG - Rizki Damir Mustika; Jonnardi (Jurnal Kontemporer Akuntansi, 2023)
This study aims to prove and empirically examine the effect of liquidity, company operating complexity, capital structure and profitability on audit report lag in non-bank companies listed on the Indonesia Stock Exchange for the period 2014 – 2018. This study is quantitative with a purposive sampling technique. sampling. Data processing using Multiple Linear Regression through eviews 10 application. Hypothesis testing analysis was carried out partially and simultaneously. The results of this study indicate that: (1) Liquidity with CR (Current Ratio) proxy, Capital Structure with LTDER (Long Term Debt to Equity Ratio) proxy, Profitability with ROA (Return on Assets) proxy has a significant and negative effect on audit report lag in non-bank companies listed on the IDX for the period 2014-2018; (2) The complexity of the Company's Operations with the JTAP proxy (Number of Subsidiaries) has a significant and positive effect on audit report lag in non-bank companies listed on the IDX for the period 2014-2018.